An integrated approach to control a prolonged outbreak of multidrug‐resistant Pseudomonas aeruginosa in an intensive care unit. (25th October 2013) - Knoester, M.; de, M. G. J.; Maarleveld, J. J.; Claas, E. C. J.; Bernards, A. T.; de, E.; van, J. T.; Veldkamp, K. E.; Allerberger, F.
Abstract In this paper we aim to provide insight into the complexity of outbreak management in an intensive care unit (ICU) setting. In October 2010 four patients on the ICU of our tertiary care centre were colonized or infected with a multidrug‐resistant strain of Pseudomonas aeruginosa (MDR‐PA). An outbreak investigation was carried out and infection control measures were taken in an attempt to identify a potential source and stop transmission. The outbreak investigation included descriptive epidemiology, comprising retrospective case finding by reviewing the laboratory information system back to 2004 and prospective case finding by patient screening for MDR‐PA. Furthermore, microbiological analysis, environmental screening and a case‐control study were carried out. Infection control measures consisted of re‐education of healthcare personnel on basic hygiene measures, auditing of hygiene procedures used in daily practice by infection control practitioners, and stepwise up‐regulation of isolation measures. From February 2009 to January 2012, 44 patients on our ICU were found to be MDR‐PA positive. MDR‐PA isolates of the 44 patients showed two distinct AFLP patterns, with homology within each of the AFLP clusters of more than 93%. The VIM metallo‐β‐lactamase gene was detected in 20 of 21 tested isolates. A descriptive epidemiology investigation identified the rooms with the highest numbers of MDR‐PA positive patients. The case‐control study showed three factors to be independently associated with MDR‐PA positivity: admission to ICU subunit 1 (OR, 6.1; 95% CI, 1.7, 22), surgery prior to or during admission (OR, 5.7; 95% CI, 1.6, 20) and being warmed‐up with the warm‐air blanket (OR, 3.6; 95% CI, 1.2, 11). After three environmental screening rounds, with sampling of sinks, furniture and devices in the ICU, without revealing a clear common source, a fourth environmental investigation included culturing of faucet aerators. Two faucets were found to be positive for MDR‐PA and were replaced. The occurrence of new cases decreased with the strengthening of infection control measures and declined further with the removal of the common source. With this integrated approach a prolonged outbreak of P. aeruginosa was controlled. Contaminated faucet aerators on the ICU probably served as a persisting source, while interpatient transmission by medical staff was a likely way of spread. Seven months after the last case (January 2012) and 3 months after cessation of extended isolation measures (May 2012), single cases started to occur on the ICU, with a total of seven patients in the past year. No common source has yet been found.